A photosynthesis continuous monitoring system for CAM plants - Cheng, Yongsan; He, Dongxian (International Journal of Agricultural and Biological Engineering, 2019)
Diurnal CO2 exchanges in crassulacean acid metabolism (CAM) plants are significantly different from those in C3 and C4 plants. The instantaneous short-time CO2 exchange of a single leaf measured by commercial portable photosynthesis measuring systems with a small leaf chamber cannot reflect the plant photosynthetic capacity for CAM plants because of the CO2 fixation property. Therefore, a photosynthesis continuous monitoring system with two canopy cuvettes was developed for measuring diurnal net CO2 exchange rates for CAM plants. To evaluate stability and applicability of the photosynthesis continuous monitoring system, continuous measurement of net CO2 exchange rates of plants with different photosynthetic pathways were conducted. An obligate CAM plant (Kalanchoe daigremontiana), four facultative CAM plants (Dendrobium officinale, D. chrysotoxum, D. nobile, and D. primulinum), a C3 plant (Strawberry, Fragaria ananassa), and a C4 plant (Corn, Zea mays) were selected as model plants. K. daigremontiana had a significant CO2 absorption during the dark period and its net CO2 exchange rates fluctuated around 0 μmol/(m2•s) during the photoperiod in a growth chamber. Net CO2 exchange rates of F. ananassa and Z. mays in a greenhouse gradually increased after sunrise, reaching a maximum at about 12:00, and then gradually decreased to negative values during the night time. It is interesting to observe that D. officinale in the greenhouse and growth chamber absorbed CO2 during both day and night times. The photosynthetic pathways of D. chrysotoxum, D. nobile, and D. primulinum were also well distinguished by this photosynthesis continuous monitoring system. The results showed that the photosynthesis continuous monitoring system is capable for quantitative evaluation of diurnal net CO2 exchange characteristics not only in the CAM plants but also in small size C3 and C4 plants with low net photosynthetic rates for long-time and high-accuracy measurements. Keywords: diurnal net CO2 exchanges, infrared CO2 analyzer, mass airflow meter, net photosynthetic rate, photosynthetic pathway DOI: 10.25165/j.ijabe.20191203.4885 Citation: Cheng Y S, He D X. A photosynthesis continuous monitoring system for CAM plants. Int J Agric & Biol Eng, 2019; 12(3): 141–146.